2009
DOI: 10.1051/0004-6361/200912524
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of intrinsic Li depletion and Li-Na anti-correlation in the metal-poor globular cluster NGC 6397

Abstract: Context. To alleviate the discrepancy between the prediction of the primordial lithium abundance in the universe and the abundances observed in Pop II dwarfs and subgiant stars, it has been suggested that the stars observable today have undergone photospheric depletion of lithium. Aims. To identify the cause of this depletion, it is important to accurately establish the behaviour of lithium abundance with effective temperature and evolutionary phase. Stars in globular clusters are ideal objects for such an abu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
337
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(381 citation statements)
references
References 62 publications
(108 reference statements)
43
337
1
Order By: Relevance
“…A MgAl anti-correlation has not been identified in NGC 6397, but Mg also seems to exhibit a certain scatter (Korn et al 2007). Lind et al (2009), hereafter Paper I, presented Na abundances for >100 TO, SGB, and RGB stars, and found that the most heavily Na-enriched stars are also significantly depleted in Li. It is thus clear that NGC 6397, like other globular clusters, should no longer be regarded as a single stellar population despite the tightness of its colour-magnitude diagram.…”
Section: Introductionmentioning
confidence: 99%
“…A MgAl anti-correlation has not been identified in NGC 6397, but Mg also seems to exhibit a certain scatter (Korn et al 2007). Lind et al (2009), hereafter Paper I, presented Na abundances for >100 TO, SGB, and RGB stars, and found that the most heavily Na-enriched stars are also significantly depleted in Li. It is thus clear that NGC 6397, like other globular clusters, should no longer be regarded as a single stellar population despite the tightness of its colour-magnitude diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Richard et al 2005), we find strong support for the need of some turbulence, with strict limits to its efficiency (cf. figure 10 in Lind et al 2009b). In absence of macroscopic turbulence, the turnoff and subgiant stars would deplete too much lithium compared to more unevolved stars, giving rise to large (∼0.6 dex) variations in surface-lithium abundance with evolutionary phase, which are not reproduced by observations.…”
Section: Results and Implicationsmentioning
confidence: 96%
“…For approximately one third of the sample we also covered the Na doublet at 8183Å and 8194Å, which is a fundamental ingredient to properly disentangle between in situ depletion and pre-enrichment effects (by testing the existence of a Li-Na anticorrelation, if any). More details about the observations and the reduction of the data set can be found in Lind et al (2009b).…”
Section: Iaus266 the Lithium History Of Ngc 6397mentioning
confidence: 99%
“…The first evidence rests on the chemical analysis that reveals large star-to-star abundance variations in light elements in all individual clusters studied so far, while the iron abundance stays constant (for a review see Gratton et al 2004). These variations include the well-documented anticorrelations between C-N, O-Na, Mg-Al, Li-Na and F-Na (Kraft 1994;Carretta et al 2007;Gratton et al 2007;Carretta et al 2006;Bonifacio et al 2007;Lind et al 2009). This global chemical pattern requires H-burning at high temperature around 75 × 10 6 K (Arnould et al 1999;Prantzos et al 2007).…”
Section: Chemical Enrichment Of Globular Clustersmentioning
confidence: 99%